RESPON DOSEN PGMI TERHADAP PENDIDIKAN ANTIKORUPSI KEDALAM KURIKULUM PERGURUAN TINGGI ISLAM - Yuni Setia Ningsih (PIONIR: JURNAL PENDIDIKAN, 2021)
Anti-corruption education has become a serious concern of the government. The Indonesian government is trying to include anti-corruption education in the higher education curriculum. The education will be included in the higher education curriculum by considering the curriculum content in each university. This needs discussions and opinions to ascertain the position of anti-corruption education in the curriculum. Therefore, it is necessary to conduct research on the urgency of anti-corruption education into the curriculum of Islamic higher education. This study aims to determine the opinion of PGMI lecturers about the urgency of anti-corruption education into the Islamic higher education curriculum, especially PGMI. This research is a qualitative research with a descriptive approach. The data collection technique used was distributing questionnaires, interviews, and document analysis. The instruments used were questionnaire sheets, interview lists, and documents. The collected data were analyzed using the Miles and Huberman model, namely: data collection, data reduction, data display, and drawing conclusions. Based on the research data, it was found that the PGMI FTK lecturers of UIN Ar-Raniry had high attention and gave a positive response to the urgency of anti-corruption education into the curriculum of Islamic higher education. Furthermore, it is also known that the dominant respondents (as many as 58%) stated that anti-corruption education is necessary or urgent to be included in the curriculum of Islamic higher education. Finally, the curriculum model suggested by the respondents is an integrated, a habituation, and an autonomous independent model to accommodate anti-corruption education.